THE DEVELOPMENT OF FOOD PRODUCTION TEACHING MATERIALS FOR CLASS III ELEMENTARY SCHOOL STUDENTS - Anggara Dwinata; Emy Yunita Rahma Pratiwi; Abdur Rahman As’ari; Cholis Sa’dijah; Abdul Halim Abdullah (Graduate School of Universitas Negeri Malang, 2022)
This study-aims to obtain contextual-based thematic teaching materials that are suitable and easy for teachers and students to learn. Teaching materials must meet the requirements of validity, practicality, and effectiveness. The teaching material chosen is thematic learning, with the sub-theme of developing food production technology. The contents and contents focus on the food potential of the Tulungagung area. The-research method used in the development of teaching materials is Dick & Carey. The result showed that the teaching materials met very valid criteria based on material expert and learning designs, practical criteria based on teacher and student responses, and effective based on improving student learning outcames.